Southern green cultural criminology and environmental crime prevention: representations of nature within four Colombian indigenous communities - Rodríguez Goyes, David (Critical criminology, 2021)
This exploratory study develops a "southern green cultural criminology" approach to the prevention of environmental harms and crimes. The main aim is to understand differing cultural representations of nature, including wildlife, present within four Colombian Indigenous communities to evaluate whether they encourage environmentally friendly human interactions with the natural world, and if so, how. The study draws on primary data gathered by the Indigenous authors (peer researchers) of this article via a set of interviews with representatives of these four communities. We argue that the cosmologies that these communities live by signal practical ways of achieving ecological justice and challenging anthropocentrism.